THE ENCOUNTER OF FAITH AND ISLAM AND CATHOLICISM TOWARDS TRUE RELIGIOUS MODERATION - Abdullah Abdullah (International Conference on Social and Islamic Studies, 2021)
The encounter of faith in Islam and Catholicism towards the moderation of true religion aims to find common ground in a normative and substantial manner in order to minimize disharmony in the relationship between adherents of Islam and adherents of Catholicism. The main problem is what is the pattern of encountering faith in Islam and in Catholicism in order to build true religious moderation? This research is based on the object, pure library research, with descriptive-analytical form. The method used is manuscript review. The approach taken is a rational theological approach. The theoretical framework used is the theory of inclusiveness. This research is qualitative in nature, that is, it focuses on comparative analysis of the concept of encounter of faith in Islam and in Catholicism. The results of this study indicate that first, the encounter of faith is exoteric, namely mutual belief in the six pillars of faith, including; the pillars of faith in Islam (faith in Allah, faith in angels, faith in holy books, faith in prophets and apostles, faith in the hereafter and faith in good destiny and bad destiny, while the pillars of faith in Catholicism (Believe in God the Father, Believe in Jesus Christ, Believe in the Holy Spirit, Believe in the Church, Confession of baptism, Resurrection of the dead and the afterlife. Second, the esoteric and historical encounter, in their epistemological perspective, these two religions have Abrahamic religious origins or monotheistic religion. The concept of divinity both believes in God Almighty, only in a different perspective in terms of the functionality of His divinity. In the dimension of divinity is substantially one but in the normative labeling or giving of symbols there are different understanding implications such as the concept, the Oneness of Allah in Islam is as the One but has the nature of twenty and ninety-nine names (asma alhusna) while in Catholicism it is understood that God is One but functionality three (Trinity). Third, the concept of the encounter of faith in Islam and in Catholicism as a religion of salvation, both religions believe that the faith of each religion has the same doctrine of the Unity of God as the Authority of all, granting salvation to whomever He wills. Belief in salvation as a form of encounter of faith is literally known as salam (Arabic) and shalom (Hebrew). In Islam, it is believed that the end of the human journey is death and after death will be given a safe reward for those who obey His commands as explained in the Qur'an letters (2): 71, 102, 112, (3): 19, 20, (4): 65, 90 , 91, (5): 3, 16, and the Koran letter (6): 14, 35. While in the Bible it is explained; Matthew 8:1-4, 14-17, Mark 1:40-45, and Luke 5:12-16. Fourth, to create true religious moderation, it is hoped that all religious adherents, both from Islam and from Catholic circles, from congregations to religious leaders, have a religious understanding that is pluralist, esoteric in theology and synchronic in society as well as harmony in living together in order to build life. a safe and peaceful religion and nation that is full of tolerance on the basis of love.